El procedimiento administrativo sancionatorio en el marco de las empresas de servicios públicos domiciliarios: aproximación teórica a sus postulados básicos (2020)
The Superintendency of Domestic Utilities is responsible for the inspection, surveillance, and control of domestic utilities companies. Within this context, this administrative authority has the power to impose sanctions on such providers, for which it uses the general administrative sanction procedure enshrined in Law 1437 of 2011, in accordance with other rules of substantial order dispersed in the national regulatory system, which determine the sanctions to be imposed, but especially the criteria under which said power must be exercised. However, there is insufficient clarity as to whether the way in which these legal instruments are laid down actually leads to the fulfilment of the basic tenets of any administrative sanctioning procedure, that is, whether the principle of legality, typicity, timeliness, gradualness, the right of legal defense, the non bis in idem and other guarantees inherent in the due process that must precede the imposition of the sanctions that may be imposed on domestic utilities, are actually guaranteed. And it is within this context that this article offers an approximation to the legal and theoretical elements that make it possible to define whether the administrative sanctioning procedure in question satisfies the basic postulates that must be inherent in this type of action.